Modelling of concepts "purpose", "goal", "task", and "function" in law - Čyras, Vytautas (Lietuvos matematikos rinkinys, 2004)
The formalisation of concepts a ``purpose'',  ` `  goal'', `  `  task'', and ```  `  function'' in law is examined. Conceptual graphs called ``  `  goal-task graphs'' are proposed to model them. A goal is associated with a predicate, which characterises the goal. A node represents a state, in which the predicate is true. An edge represents the task. A task e = (u, v) represents a mean to implement the state v, which assumes u.
Keywords: goal modelling; informatics in law; formalisation of concepts in law